Estudo preliminar do efeito do consumo forçado de etanol sobre a dieta nutricional de rato macho adulto Wistar - Castagnaro, Luciana Regina; Santiago, Karina Basso [UNESP]; Augusto, Ricardo Sgarbi; Soares, Vanessa Mendonça [UNESP]; Pereira, Juliano Gonçalves [UNESP]; Martins, Otávio Augusto [UNESP]; Biondi, Germano Francisco [UNESP] (My University, 2010)
In the preliminary study was used male Wistar rats to evaluate the effect of forced ethanol consumption to 10% on the nutritional diet. We measured the body mass, food intake, consumption of filtered water ad libitium, and consumption of ethanol solution to 10%. The analysis showed changes in fluid intake (water and ethanol solution 10%) in food intake and body mass. Based on the results, we conclude that the solution of ethanol influenced the nutritional parameters of male Wistar rats.

No estudo preliminar foi utilizado rato macho da linhagem Wistar com o objetivo de avaliar o efeito do consumo forçado de etanol a 10% sobre a dieta nutricional. Foram mensurados a massa corpórea, consumo de ração, consumo de água filtrada ad libitium, e consumo de solução de etanol a 10%. A análise apresentou alterações no consumo de líquidos (água e solução de etanol a 10%), no consumo alimentar e na massa corpórea. Com base nos resultados, conclui-se que a solução de etanol influenciou os parâmetros nutricionais dos ratos machos da linhagem Wistar.
Preliminary study of the effect of forced ethanol consumption on the nutritional diet of adult male Wistar rat
Keywords: Nutrition; Rat; Alcohol; Diet; Nutrição; Rato; Álcool; Dieta